2011
DOI: 10.1007/s00296-011-1965-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of human xanthine oxidoreductase (HXOR), anti-HXOR antibodies, and microorganisms in synovial fluid of patients with joint inflammation

Abstract: This work is to investigate the levels of human xanthine oxidoreductase (HXOR), its antibodies, and microorganisms in synovial fluid of patients with untreated rheumatoid joint diseases. Synovial fluids were collected from sixty-four patients with rheumatoid joint diseases. Sixty-four age-matched individuals were included as control. Xanthine oxidoreductase (XOR) proteins level and anti-XOR antibodies were determined in the blood and synovial fluid, using human XOR as antigen, by enzyme-linked immunosorbent (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…The highest percentage of immune complexes IgG-XOR was recorded in mechanical infections and the hemarthrosis category, and was close to the rest of the groups. These results confirm our previous study (10,35) where the presence of these antibodies was well discussed. Al Muhtaseb et al (35) indicated that anti-XO antibodies in SF possess a protective role in inflammatory arthritis, where they play a role in eliminating XOR from SF.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The highest percentage of immune complexes IgG-XOR was recorded in mechanical infections and the hemarthrosis category, and was close to the rest of the groups. These results confirm our previous study (10,35) where the presence of these antibodies was well discussed. Al Muhtaseb et al (35) indicated that anti-XO antibodies in SF possess a protective role in inflammatory arthritis, where they play a role in eliminating XOR from SF.…”
Section: Discussionsupporting
confidence: 93%
“…These results confirm our previous study (10,35) where the presence of these antibodies was well discussed. Al Muhtaseb et al (35) indicated that anti-XO antibodies in SF possess a protective role in inflammatory arthritis, where they play a role in eliminating XOR from SF. However, immune complexes could activate complement and participate in propagating the inflammatory cycle.…”
Section: Discussionsupporting
confidence: 93%